2013
DOI: 10.1176/appi.ajp.2013.12081135
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Working Memory and Altered Brain Activation in Persons at Risk for Psychosis

Abstract: Despite comparable behavioral performance, at-risk participants performing a verbal working memory task exhibited altered brain activation compared with healthy subjects. These findings demonstrate an altered pattern of brain activation in at-risk persons that contains elements of reduced function as well as compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 83 publications
(84 reference statements)
8
21
1
Order By: Relevance
“…Consistent with our results Yaakub et al (Yaakub et al, 2013) observed increased taskrelated deactivation in the PCC during a working memory task in UHR subjects relative to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results Yaakub et al (Yaakub et al, 2013) observed increased taskrelated deactivation in the PCC during a working memory task in UHR subjects relative to controls.…”
Section: Discussionsupporting
confidence: 93%
“…The percentages of CHR individuals in our cohort who had scores equal or lower than 6 on the GFS:S and GSF:R were 43.2 and 44.4%, respectively. These social and role outcomes were similar to those of other CHR cohorts (Carrion et al, 2013) as were our rates of conversion to psychosis and exposure to antipsychotic medications (Niendam et al, 2013;Dandash et al, 2013;Yaakub et al, 2013). One CHR individual was scanned around the time of conversion to psychosis.…”
Section: Participantssupporting
confidence: 70%
“…These regions belong to frontostriatal networks found repeatedly to be abnormal in PET studies of CHR cohorts (Fusar-Poli et al, 2012). Our finding that the CHR and control groups did not differ in terms of behavioral performance is neither surprising (Wilkinson and Halligan, 2004), as our task had low cognitive demand by design, nor unique to our at-risk cohort (Yaakub et al, 2013).…”
Section: Neural Dysfunction In Cognitive Control Circuits T Colibazzimentioning
confidence: 61%
“…Focal grey matter volume reductions were described in several brain areas partially predicting the transition to psychosis. [39][40][41]48 Using fMRI, Yaakub and colleagues 49 observed hypoactivation in the left anterior insula during a working memory task in ARMS patients compared with healthy controls, but they found no significant differences in behavioural performance. In a study by Schmidt and colleagues, 50 abnormal frontoparietal connectivity during a working memory task became evident in an ARMS sample and was found to be related to the severity of psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Yaakub and colleagues 49 similarly found hypoactivation in the left anterior insula during a working memory task in ARMS patients without observing differences in behavioural performance. 49 In general, forthcoming longitudinal studies should involve medication-naive FEP patients to further unravel the developmental process of meta-and neurocognitive deficits as well as underlying neuronal activation patterns.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 96%